KRITIK IBN WARRAQ ATAS ORIENTALISME EDWARD SAID: PERDEBATAN EPISTEMOLOGIS MENGENAI ‘TIMUR DAN BARAT’ - Media Zainul Bahri (UIN Raden Mas Said Surakarta, 2019)
This article tries to describe Ibn Warraq's critique onEdward Said's monumental work,